2021
DOI: 10.3389/fneur.2021.808568
|View full text |Cite
|
Sign up to set email alerts
|

VEGF Modulates Neurogenesis and Microvascular Remodeling in Epileptogenesis After Status Epilepticus in Immature Rats

Abstract: Neurogenesis and angiogenesis are widely recognized to occur during epileptogenesis and important in brain development. Because vascular endothelial growth factor (VEGF) is a critical neurovascular target in neurological diseases, its effect on neurogenesis, microvascular remodeling and epileptogenesis in the immature brain after lithium-pilocarpine-induced status epilepticus (SE) was investigated. The dynamic changes in and the correlation between hippocampal neurogenesis and microvascular remodeling after SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Enhanced expression of vascular endothelial growth factor (VEGF) has been reported in hippocampal slices from patients with drug-resistant epilepsy [ 37 ]. Consistently, reduced cerebral blood flow and tissue hypoxia can trigger an increased expression of VEGF in vascular endothelial cells, thus inducing abnormal angiogenesis and increasing microvascular structural density during epileptogenesis [ 38 ]. It is suggested that this adaptative process may improve perfusion and meet the heightened metabolic demands of neurons.…”
Section: Changes Of the Neurovascular Unit In Epileptogenesismentioning
confidence: 99%
“…Enhanced expression of vascular endothelial growth factor (VEGF) has been reported in hippocampal slices from patients with drug-resistant epilepsy [ 37 ]. Consistently, reduced cerebral blood flow and tissue hypoxia can trigger an increased expression of VEGF in vascular endothelial cells, thus inducing abnormal angiogenesis and increasing microvascular structural density during epileptogenesis [ 38 ]. It is suggested that this adaptative process may improve perfusion and meet the heightened metabolic demands of neurons.…”
Section: Changes Of the Neurovascular Unit In Epileptogenesismentioning
confidence: 99%
“…Another target of HIF activity in reactive neonatal astrocytes that contributes to enhancing endogenous restorative mechanisms is VEGF, the aforementioned factor that stimulates the formation of new blood vessels to compensate for oxygen deficiencies in the affected nervous tissue. However, as demonstrated by numerous in vitro and in vivo studies, VEGF can promote neurogenesis [95][96][97][98], directly supporting tissue repair. In this context, the induced astrocytic reactivity associated with HIF activation is beneficial for neuroregeneration.…”
Section: Astrocyte Reactivity In Neurodevelopmental Disordersmentioning
confidence: 99%
“…Within this region of the brain, increased levels of VEGF promote neurogenesis and microvascular remodeling, amongst other beneficial effects. This could have implications for a variety of conditions including status epilepticus and Alzheimer's disease [34][35][36]. Within the eye, it was shown that VEGF conferred some degree of neuroprotection against dry eye disorders.…”
Section: Neuroprotective Effects Of Omega-3 Fatty Acidsmentioning
confidence: 99%